The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s11934-020-01009-7
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil Alone or in Combination with Tamsulosin for the Management for LUTS/BPH and ED

Abstract: Purpose of Review Aim of our systematic review is to evaluate and summarize the efficacy and safety of tadalafil alone or in combination with tamsulosin for the management of lower urinary tract symptoms (LUTS)/benign prostatic hyperplasia (BPH) and erectile dysfunction (ED). Recent Findings Daily tadalafil, in particular 5 mg, according to retrieved studies, appears to be both safe and effective in treating LUTS/BPH and ED, compared with placebo or tamsulosin. The combination of daily tadalafil 5 mg and tam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 41 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…These include sildenafil, tadalafil, vardenafil, and avanafil, which differ for bioavailability, pharmacokinetics, affinity, and selectivity for PDE isoenzymes. Sildenafil is mostly used on demand, due to its short bioavailability, while tadalafil can be used daily and could be preferred in patients with contemporary benign prostatic hyperplasia [33]. It is noteworthy that PDE5 is involved in the intracellular signaling of insulin.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…These include sildenafil, tadalafil, vardenafil, and avanafil, which differ for bioavailability, pharmacokinetics, affinity, and selectivity for PDE isoenzymes. Sildenafil is mostly used on demand, due to its short bioavailability, while tadalafil can be used daily and could be preferred in patients with contemporary benign prostatic hyperplasia [33]. It is noteworthy that PDE5 is involved in the intracellular signaling of insulin.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Although these drug treatments are effective, they can cause troublesome adverse reactions, such as hypotension, dizziness, and sexual dysfunction (7,8). Tadalafil, one of the phosphodiesterase type 5 inhibitors (PDE5Is) used to improve the symptoms of erectile dysfunction (ED), has been increasingly investigated and gained approval for the treatment of BPH in many countries since 2011 (9). This is mainly because PDE5Is are believed to likely act mainly by increasing the concentration of nitric oxide (NO), which improves the activity of intracellular cyclic guanosine monophosphate (cGMP) (10).…”
Section: Introductionmentioning
confidence: 99%
“…Although these drug treatments are effective, they can cause troublesome adverse reactions, such as hypotension, dizziness, and sexual dysfunction ( 7 , 8 ). Tadalafil, one of the phosphodiesterase type 5 inhibitors (PDE5Is) used to improve the symptoms of erectile dysfunction (ED), has been increasingly investigated and gained approval for the treatment of BPH in many countries since 2011 ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, tadalafil 5 mg daily treatment as monotherapy or in combination with α-blockers have shown efficacy in treating both LUTS and ED. Sebastianelli et al indicated that tadalafil 5 mg should be considered a primary treatment option for patients with LUTS/BPH and ED with an excellent tolerability, safety, and effectiveness profile, both alone or in combination with tamsulosin 0.4 mg ( 5 ). Tadalafil is not just a treatment alternative to other established drugs for LUTS that have some sexual adverse events associated with their use, it is the only drug that can treat both ED and LUTS at the same time ( 6 ).…”
mentioning
confidence: 99%